Determinants of Managerial Performance in The Covid-19 Era - Gani, Nur Asni; Priharta, Andry (Technium Social Sciences Journal, 2023)
This study examines the determinants of managerial performance which consist of management control systems, organizational culture, and organizational commitment. The analysis was carried out using multiple linear regression with the SPSS version 22 program. The object studied was a health care institution in the South Tangerang area with data collected from 52 respondents. The results of the study show that partially, the management control system, organizational culture and organizational commitment have a significant positive effect on managerial performance. Simultaneously, all independent variables have a significant effect on managerial performance.